2014
DOI: 10.1080/17508975.2014.918870
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality in London schools. Part 1: ‘performance in use’

Abstract: This study aims to assess the adequacy of current guidelines, framed around thermal comfort, estimated ventilation rates, and CO 2 levels, for the provision of indoor air quality (IAQ) in school classrooms. It draws on detailed monitoring data from a sample of 18 classrooms from 6 London schools. Overheating during the non-heating season was identified in eight south-, south-east-, and east-facing classrooms in two Victorian and two contemporary schools. Four classrooms in these contemporary schools also faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…They remain consistent with the observation of Konopinski (1985) for formaldehyde in one office building in the US. They are also consistent with what was already observed in schools for benzene and formaldehyde (Canha et al, 2016), and terpenes (Chatzidiakou et al, 2014), as well as in dwellings for benzene (Langer et al, 2016), formaldehyde (Salthammer et al, 2010), terpenes (Schlink et al, 2010), O 3 (Cattaneo et al, 2011), and NO 2 (Cattaneo et al, 2011;WHO, 2010). Even if office buildings are expected to be more controlled environments due to the presence of HVAC systems compared to schools and dwellings, the season nevertheless shows an effect.…”
Section: Table 2asupporting
confidence: 91%
“…They remain consistent with the observation of Konopinski (1985) for formaldehyde in one office building in the US. They are also consistent with what was already observed in schools for benzene and formaldehyde (Canha et al, 2016), and terpenes (Chatzidiakou et al, 2014), as well as in dwellings for benzene (Langer et al, 2016), formaldehyde (Salthammer et al, 2010), terpenes (Schlink et al, 2010), O 3 (Cattaneo et al, 2011), and NO 2 (Cattaneo et al, 2011;WHO, 2010). Even if office buildings are expected to be more controlled environments due to the presence of HVAC systems compared to schools and dwellings, the season nevertheless shows an effect.…”
Section: Table 2asupporting
confidence: 91%
“…A detailed description of the school sample, and inferential statistics on indoor and outdoor concentrations can be found in previous publications. 4,5 Case studies…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed description of the sample selection of schools and classrooms has been published previously. 4 Data on building characterisation included information on: the microclimate; construction characteristics; maintenance and operation of school buildings; and occupancy patterns (Table 3). The data were collected from onsite observations and standardised checklists administered as semi-structured interviews to school occupants involved with daily maintenance and operation of the schools and classrooms, such as classroom teachers, headteachers and facility managers.…”
Section: Collection Of Building Characteristics Maintenance and Opermentioning
confidence: 99%
“…Several studies on indoor air quality in school and kindergarten environments have been conducted (Darus et al 2012;Zwoździak et al 2013;Chatziadiakou et al 2015), and other studies have also shown that there is a relationship between indoor air quality and the safety of students and teachers in schools (Salameh et al 2015;Lin et al 2017). These studies highlighted the value of monitoring air quality in a school setting, with the main objective being to minimize the exposure of students to air pollution and to better understand the technique to be used to mitigate the decline in indoor air quality to establish a more favorable, healthy, and efficient school atmosphere and to ensure student and staff safety.…”
Section: Introductionmentioning
confidence: 99%